Developing Students’ Writing Skill By Using Picture Media - winda Widyaningrum; Astri Indriana Octavita (LPPM Universitas Mohammad Husni Thamrin, 2019)
Writing is one of the basic skills in learning English. For some students learning writing is still difficult, especially how to develop ideas into interesting writing. A teacher must be able to apply learning methods that are fun and actively involve students in the learning process, also use appropriate learning media that it can attract students’ interest to make learning writing easier. This research is aimed to understand how to develop students’ writing skill by using picture as an alternative media. The method of the research is a classroom action research. It used three cycles and each cycle consisted of four steps; planning, acting, observation and reflecting. It was conducted at the Teacher College with the total population 50 students. Data needed was obtained from observation, interview and test. The result of the test has shown that there is positive feedback given from students through the use of picture media in writing teaching. It can be proven by the result of the test in each cycle which shown. The first cycle, the students got the average score 71,3 (43%). In the second cycle, they got the average score 74,6 (71,4%). While in the third cycle, they got 76,8 (90,5%). Base on the fact above the researcher concluded that picture media is effective to develop students’ writing skill.